Analiza finansowa gospodarki wodno-ściekowej w gminie Czarny Bór = Financial analysis of water and sewage economy of the Czarny Bor commune - Warężak, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper it was described the results of water and wastewater management analysis on the example of the development strategy of the commune. The models present solutions based on balance of pollution loads and the investments cost. Probability of the investment realization were comparised with the financial possibilities of the municipal budget and potential grants sources.
Keywords: gospodarka wodno-ściekowa; analiza ekonomiczna inwestycji; water and wastewater management; economic analysis of investments